2007
DOI: 10.1097/cad.0b013e32825209f6
|View full text |Cite
|
Sign up to set email alerts
|

5-Bromo-2-deoxyuridine activates DNA damage signalling responses and induces a senescence-like phenotype in p16-null lung cancer cells

Abstract: 5-Bromo-2-deoxyuridine (BrdU) is a thymidine analogue that is incorporated into replicating DNA. Although originally designed as a chemotherapeutic agent, sublethal concentrations of BrdU have long been known to alter the growth and phenotype of a wide range of cell types. Mechanisms underlying these BrdU-mediated effects remain unknown, however. We have characterized the effects of BrdU on A549 lung cancer cells by examining DNA damage responses, cell cycle effects and phenotypic changes. A549 cells express w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
(57 reference statements)
5
28
0
Order By: Relevance
“…We found that cells exposed to the direct DNA-damageinducing agent BrdU induced standard senescence markers, such as p21, fibronectin, IL8 and others, as reported previously (Masterson and O'Dea, 2007;Eriko et al, 1999;Suzuki et al, 2001), and that they are positive for SA-b-gal and show enhanced secretion of IL8 (Cho et al, 2011), which is similar to what is observed in senescent cells generated by other approaches (Coppé et al, 2008). We utilized this unique direct DNA damage approach to activate senescence in cancer cells to determine whether ATM kinase and ROS play distinct roles in the initiation and maintenance of senescence.…”
Section: Discussionsupporting
confidence: 89%
“…We found that cells exposed to the direct DNA-damageinducing agent BrdU induced standard senescence markers, such as p21, fibronectin, IL8 and others, as reported previously (Masterson and O'Dea, 2007;Eriko et al, 1999;Suzuki et al, 2001), and that they are positive for SA-b-gal and show enhanced secretion of IL8 (Cho et al, 2011), which is similar to what is observed in senescent cells generated by other approaches (Coppé et al, 2008). We utilized this unique direct DNA damage approach to activate senescence in cancer cells to determine whether ATM kinase and ROS play distinct roles in the initiation and maintenance of senescence.…”
Section: Discussionsupporting
confidence: 89%
“…Pulse-chase analysis demonstrated that CD49f bright /Sca1 1 /ALDH 1 -derived rimmed clones contained rare LRCs and abundant label-diluting cells (LDCs) that were localized to the clone rim ( Figures 3I and 3J). A similar distribution of LRCs and LDCs in the K5/TRE-histone 2B model ( Figure E4) indicated that BrdU toxicity did not affect proliferation of central region cells (32).…”
Section: Basal Cellsmentioning
confidence: 64%
“…Since BrdU incorporation during active DNA synthesis occurs during DNA replication and DNA repair [32], and BrdU incorporation can activate DNA damage responses [33], counting BrdU-labeled cells may overestimate the number of mitotic cells, especially when cells are undergoing apoptosis. Here, we detected elevated expression of Ki-67, a marker for cell proliferation, in the DKO but not TKO ileum and colon.…”
Section: Discussionmentioning
confidence: 99%